Pengaruh Fasilitas Belajar dan Motivasi Belajar terhadap Hasil Belajar Siswa pada Mata Pelajaran Ekonomi Kelas XI SMA Negeri 1 Sukasada - Ginting, Rena Gita Br; Santi, Ni Wayan Ayu (Ekuitas: Jurnal Pendidikan Ekonomi, 2024)
This study aims to determine the influence of learning facility variables and learning motivation on student learning outcomes in economics class XI of SMA Negeri 1 Sukasada. The population in this study is grade XI students of SMA Negeri 1 Sukasada. In this study, the sample to be used is all students in grade XI of SMA Negeri 1 Sukasada which totals 39 students. The sampling technique in this study is a saturated sampling technique. The data in this study was collected by distributing questionnaires. The analysis technique used is multiple linear regression analysis with partial hypothesis tests (t test) and simultaneous (F test). The results showed that: (1) Learning Facilities partially had a positive and significant effect on learning outcomes, with a significant value of 0.001<0.05 (2) Learning Motivation partially had a positive and significant effect on learning outcomes, with a significant value of 0.011<0.05 (3) Learning Facilities and Learning Motivation simultaneously had a positive and significant effect on learning outcomes, with a significant value of 0.000<0.05.